Pengaruh Dewan Komisaris Independen dan Komite Audit terhadap Manajemen Laba pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Tahun 2015-2017 - Anton Ferry Ananda; Santi Andriani (JAMIN : Jurnal Aplikasi Manajemen dan Inovasi Bisnis, 2019)
This study aims to determine the effect of independent commissioners and audit committees on earnings management. This research uses quantitative methods. The data used in this study are secondary data, i.e. data obtained through existing sources and do not need to be collected by the researcher themselves. The data is in the form of an annual report issued by companies listed in the 2015-2017 period which are listed on the Indonesia Stock Exchange. The population in this study are manufacturing companies listed on the Indonesia Stock Exchange in the 2015-2017 period. The results showed that the independent board of commissioners and the audit committee had no simultaneous effect on earnings management. This is consistent with the results of the simultaneous regression coefficient test (Test F) which shows the calculated F value is smaller than the F table, and with a determinant value of 3.1%. Partially the independent board of comissioners and audit committee has no effect on earnings management. Based on the results of the partial regression coefficient test (t test) on the variable independent commissioners and the audit committee showed a significance value greater than 0.05, so it was concluded that the two variables in this study had no effect on earnings management.Keywords: Audit Committee, Independent Board of Commissioners, Profit Management, Finance